Exact traveling wave solutions of a geophysical Boussinesq system. (June 2023) - Khorbatly, Bashar
Abstract: We derive the classical Boussinesq system to model equatorial water flows with the weak Coriolis effect due to Earth's rotation. The system is derived from the Zakharov–Craig–Sulem formulation of the water wave equations in the f -plane approximation. Then, for the obtained system, we find some exact traveling wave solutions of the form s e c h 2 and s e c h .